Implantable cardiac defibrillator and mortality in non-ischaemic cardiomyopathy: an updated meta-analysis. Issue 3 (5th August 2017) - Alba, Ana C; Foroutan, Farid; Duero Posada, Juan; Battioni, Luciano; Schofield, Toni; Alhussein, Mosaad; Agoritsas, Thomas; Spencer, Frederick A; Guyatt, Gordon
Abstract : Objectives: The benefit of implantable cardiac defibrillator (ICD) in symptomatic patients with systolic dysfunction and non-ischaemic cardiomyopathy remains controversial. We conducted a systematic review and meta-analysis to determine the effect of ICD in patients with non-ischaemic cardiomyopathy on (1) all-cause mortality, (2) cardiovascular mortality and (3) sudden cardiac death. Methods: We searched citations in meta-analyses published until 2012, and in MEDLINE, Embase, PubMed and Cochrane databases from 2012 to October 2016. We included randomised controlled trials (RCTs) evaluating the effect of ICD therapy on all-cause and cardiovascular mortality and sudden cardiac death in patients with non-ischaemic cardiomyopathy. Independent reviewers evaluated study eligibility, abstracted data and assessed risk of bias in duplicate. We used random-effect models to meta-analyse relative risks (RR) and hazard ratios (HR) across studies, the Grades of Recommendation, Assessment, Development, and Evaluation system to quantify absolute effects and quality of evidence, and I 2 to evaluate heterogeneity. Results: We identified six RCTs including 1715 patients experiencing 421 deaths. ICD therapy was associated with reduced overall mortality (HR 0.78, 95% CI 0.66 to 0.92, I 2 = 0%, risk difference 4.7%, high quality), cardiovascular mortality (RR 0.77, 95% CI 0.60 to 0.98, I 2 = 39%, risk difference 3.3%, high quality) and sudden cardiac death (RR 0.45, 95% CI 0.29 to 0.70, I 2 = 0%, risk difference 4.1%, high quality). The benefit of ICD was not influenced by the use of amiodarone in the comparison group, the duration of follow-up, by use of Î²-blockers and ACE inhibitors/angiotensin receptor blocker or cardiac resynchronisation therapy. Conclusion: Primary prevention ICD therapy reduces all-cause and cardiovascular mortality and sudden cardiac death in patients with non-ischaemic cardiomyopathy.